2003
DOI: 10.1039/b310396j
|View full text |Cite
|
Sign up to set email alerts
|

The nucleobase cytosine and the cytosine dimer investigated by double resonance laser spectroscopy and ab initio calculations

Abstract: The vibronic spectrum of laser desorbed and jet cooled cytosine consists of bands from two major tautomers (keto and enol) as revealed by UV-UV and IR-UV double resonance spectroscopy and methyl blocking experiments. Only one isomer each was observed for the cytosine dimer and for the cytosine -1-methylcytosine mixed dimer. These isomers form C=OÁ Á ÁHNH/NHÁ Á ÁN hydrogen bonds. Cytosine -5-methylcytosine exhibits three isomers: one again with C=OÁ Á ÁHNH/NHÁ Á ÁN connectivity, the second with C=OÁ Á ÁHNH/NHÁ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 15 publications
14
117
2
Order By: Relevance
“…22,30 It also agrees quite well with the experimental adiabatic excitation energy of 3.95 eV estimated from the resonance-enhanced multiphoton ionization (REMPI) spectrum. 10,60 It has been proposed previously that the minimum energy path (MEP) approach is appropriate for the determination of the deactivaiton pathway since it provides information about the accessibility of the conical intersection. 29,[61][62][63] There is the possibility that it leads to the seam of CIs before reaching the ( 1 ππ*) min structure, thus providing the most relevant photochemical deactivation pathway.…”
Section: S 1 Minimum Energy Structurementioning
confidence: 99%
“…22,30 It also agrees quite well with the experimental adiabatic excitation energy of 3.95 eV estimated from the resonance-enhanced multiphoton ionization (REMPI) spectrum. 10,60 It has been proposed previously that the minimum energy path (MEP) approach is appropriate for the determination of the deactivaiton pathway since it provides information about the accessibility of the conical intersection. 29,[61][62][63] There is the possibility that it leads to the seam of CIs before reaching the ( 1 ππ*) min structure, thus providing the most relevant photochemical deactivation pathway.…”
Section: S 1 Minimum Energy Structurementioning
confidence: 99%
“…While the energy difference between the enol and keto forms is very small, some of their other properties, such as their vertical excitation energies, are very different. Nir et al reported REMPI and hole burning spectra and concluded that the keto and enol tautomers have band origins that differ by a remarkable half electron volt at 314 nm and 278 nm, respectively (42,43). The REMPI spectra of U and T exhibit a very broad structure with an onset in the frequency range of the origin of the enol cytosine first reported by Brady et al (4).. No spectroscopic detail could be extracted from these broad spectra and tautomeric information was limited for a long time to bulk measurements.…”
Section: Purinesmentioning
confidence: 99%
“…1 They produced cytosine dimers using laser desorption and presented strong evidence for only one isomer -(C1) 2 HB1 -being present in their molecular beam. 13 According to Kabelac and Hobza,54 this is the most populated isomer based on their molecular dynamics/quenching calculations (albeit of a 298K ensemble). The absence of other isomers could be explained 1 by a number of reasons stemming from the detection scheme in a REMPI experiment: (1) poor absorption in the first excited state; (2) ionization energy higher than accessible by two photons; (3) fragmentation of the cation; (4) lifetimes of the excited state being too short for second photon absorption.…”
Section: B Cytosine Dimers: Structures Binding Energies and Populationsmentioning
confidence: 99%
“…Previous ionization studies of cytosine consist of photoionization mass spectrometry (PIMS) measurements of AIEs, 6,7 photoelectron spectroscopy (PES) at the valence [8][9][10][11] and core level, 12 resonance enhanced multiphoton ionization (REMPI) experiments 13,14 and a number of electronic structure calculations. 9,[15][16][17][18] Trofimov et al 9 measured a valence-shell PES of cytosine.…”
Section: Introductionmentioning
confidence: 99%